The Relationship between Teachers' Pedagogic Competence and the Ability to Carry Out Evaluation using Anecdotal Records in Early Childhood Education Institutions - Fheby Dwi Lestari; Nopiana Nopiana; Een Yayah Haenilah (Foundation of Jannatun Naim Lampung, 2025)
This study aims to analyse the relationship between teachers' pedagogical competence with the ability to carry out learning evaluations using anecdotal records in PAUD institutions. This research is a type of research with a quantitative approach that is non-experimental and uses the correlation method. The population of this research is all teachers in Early Childhood Education (ECE) Institutions in Kota Agung Sub-district. Determination of the research sample using saturated samples with a sample size of 30 teachers. Data collection techniques using tests and questionnaires with instrument grids that have been validated by expert lecturers. The results showed that there was a relationship between the pedagogical competence of teachers with the ability to carry out evaluations using anecdotal records in PAUD institutions of 0.738. So, it can be concluded that there is indeed a significant relationship, but every teacher must improve pedagogical competence in order to be able to carry out learning evaluation more optimally